Screening economies money matters and the ethics of representation - Cuonz, Daniel 1975-; Loren, Scott 1971-; Metelmann, Jörg 1970- (transcript, 2018)
The relationship between economy, finance and society has become opaque. Quantum leaps in complexity and scale have turned this deeply interdependent web of relations into an area of incomprehensible abstraction. And while the economization of life has come under widespread critique, inquiry into the political potential of representational praxis is more crucial than ever. This volume explores ethical, aesthetic and ideological dimensions of economic representation, redressing essential questions: What are the roles of mass and new media? How do the arts contribute to critical discourse on the global techno-economic complex? Collectively, the contributions bring theoretical debate and artistic intervention into a rich exchange that includes but also exceeds the conventions of academic scholarship
Keywords: Cultural History; Cultural Studies; Culture; Finance; Mass Media; Media Aesthetics; Media Art; Media Representation; Media; New Media; Techno-Economy